The impact of industrial tuna fishing on small-scale fishers and economies in the Pacific. (September 2018) - James, Philip A.S.; Tidd, Alex; Kaitu, Lotokufaki Paka
Abstract: Industrial fishing for tuna is a major revenue earner in the Pacific Islands region. Capturing more benefits from this fishery is a key priority of Pacific Island country governments and people. Many Pacific countries have done this by allowing transhipping — the transfer of fish from industrial purse-seine fishing vessels to carrier vessels in port. This paper investigates one such port, Funafuti in Tuvalu. Using a unique dataset, the analysis (for the first time) demonstrates that there are a number of negative impacts on small-scale fishers associated with allowing transhipping in port. These negative impacts include lost employment days, reduced catches and, potentially, fresh fish availability and lower incomes within the artisanal fishery. The analysis also demonstrates that there are benefits associated with transhipping, such as spending in local businesses and bycatch off-loads. This paper provides a number of considerations for governments to optimise the benefits from transhipping and minimise costs. Highlights: Confirms indirect economic interactions between industrial fishing vessels and artisanal vessels. Transhipping brings shore-based benefits but negative impacts on artisanal fishers. Transhipping does appear to impact artisanal fishers' willingness to fish. Distribution of benefits is critical in decision making.